Vodnoekološki dejavniki regionalnega razvoja obmejnih območij ob slovensko-hrvaški meji - Plut, Dušan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2001)
Most rivers crossing the Slovene-Croatian border were in the nineties moderate to very polluted. The quality improved a little during the period 1990-1998 (mostly only for a half of the class)for Mura, Sava and lower Sotla,quality of Kolpa under Metlika worsened and quality of Dragonja did not change considerably. Pollution of the Gulf of Trieste is mostly caused by Italy and less by Slovenia and Croatia.Border waters should be treated more reasonably, primarily pollution of the same should be decreased and sustainable economy should be implemented within the range of international river basins (Sava, Drava, Mura). However from the point of view of border regional development and joint sustainable treatment of water sources, joint interstate planning and realisation of decreasing the burdening of water of Sotla, Kolpa and the Gulf of Trieste, is of the biggest importance.
Keywords: Croatia; ecology; ekologija; environmental protection; Gulf of Trieste; Hrvaška; obmejna območja; onesnaževanje okolja; onesnaževanje voda; regionalni razvoj; Slovenia; Slovenija; sustainable development; trajnostni razvoj; Tržaški zaliv; varstvo okolja